Design of the 10 PW OPCPA facility for the vulcan laser - Musgrave, I; Chekhlov, O; Collier, J; Clarke, R; Dunne, A; Hancock, S; Heathcote, R; Hernandez-Gomez, C; Galimberti, M; Lyachev, A; Matousek, P; Neely, D; et al. (2010)
We present the progress made in developing 10PW OPCPA facility for the Vulcan laser to produce pulses with focused intensities >1023 Wcm-2. This power level will be delivered by generating pulses with >300J in 30fs. These pulses will be delivered to two target areas: in one target area they will be combined with the existing Vulcan Petawatt beamline and a new target area will be created for high intensity interactions. © 2010 Optical Society of America.